FEATURES OF FOREIGN STUDENTS STUDY IN HIGH STATE EDUCATIONAL INSTITUTES OF UKRAINE - Dudchenko, N.O.; Artemenko, A.F.; Levchenko, L.Yu.; Васильєва, К.В.; Sviridyuk, V.B. (World of Medicine and Biology, 2013)
The study of features of stay of foreign students in Ukraine disrobes the row of problems the decision of which will assist bringing in on studies to Ukraine of students-foreigners, that has an important value for maintenance of scientific and educational potential of Ukrainian higher educational establishments.
Keywords: foreign students; studies